2005
DOI: 10.2166/wst.2005.0190
|View full text |Cite
|
Sign up to set email alerts
|

Acetate and ammonium diffusivity in membrane-aerated biofilms: improving model predictions using experimental results

Abstract: Membrane-aerated biofilm reactors (MABRs) are advantageous for wastewater treatment because of their ability to achieve both nitrification and denitrification in a single bioreactor. The stratification of membrane aerated biofilms, however, needs to be better understood so that MABRs can be properly designed and implemented. In this study, we present a modified multi-population model that accounts for variation in effective diffusivity in biofilms of variable biomass density. For biofilms grown at a low fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…2a, b). This heterogeneity would substantially affect model predictions for mass transfer of nutrients within the biofilm and for the rates of bacterial metabolism within the MABs [20].…”
Section: Discussionmentioning
confidence: 99%
“…2a, b). This heterogeneity would substantially affect model predictions for mass transfer of nutrients within the biofilm and for the rates of bacterial metabolism within the MABs [20].…”
Section: Discussionmentioning
confidence: 99%
“…The biofilm density was assumed to be constant through the biofilm. Biofilm density has been shown to vary with depth in an MAB containing both nitrifiers and heterotrophs (Shanahan et al, 2005); however, density in a mainly nitrifying MAB was shown to be relatively consistent through the use of FISH (Downing and Nerenberg, 2008), and therefore the density was assumed to be constant.…”
Section: Modelingmentioning
confidence: 99%
“…The highest ammonia removal at stable state did not occur at the highest mixing level for both reactors. This phenomenon can be explained by the fact that the higher shear force reduces the thickness of biofilms while facilitating the formation of denser biofilm which has a lower effective diffusivity of substrates (Shanahan et al 2005). Strong mixing was identified as the cause for the low ammonia removal in S2 in MABR1.…”
Section: Effects Of Mixingmentioning
confidence: 97%